2020
DOI: 10.1016/j.ajhg.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Localizing Components of Shared Transethnic Genetic Architecture of Complex Traits from GWAS Summary Data

Abstract: Despite strong transethnic genetic correlations reported in the literature for many complex traits, the non-transferability of polygenic risk scores across populations suggests the presence of population-specific components of genetic architecture. We propose an approach that models GWAS summary data for one trait in two populations to estimate genome-wide proportions of population-specific/shared causal SNPs. In simulations across various genetic architectures, we show that our approach yields approximately u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 95 publications
(115 reference statements)
7
65
0
Order By: Relevance
“…This is consistent with causal genetic effects tending to be similar across populations but with LD and allele frequency differences modifying marginal effect size estimates (Martin et al, 2019) . This is also consistent with trans-ethnic genetic correlations tending to be close to or not significantly different from 1 (Brown et al, 2016;Shi et al, 2020) . The most rapid path to closing gaps in PRS transferability is to increase the inclusion of GWAS participants from populations most divergent from those already routinely studied.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with causal genetic effects tending to be similar across populations but with LD and allele frequency differences modifying marginal effect size estimates (Martin et al, 2019) . This is also consistent with trans-ethnic genetic correlations tending to be close to or not significantly different from 1 (Brown et al, 2016;Shi et al, 2020) . The most rapid path to closing gaps in PRS transferability is to increase the inclusion of GWAS participants from populations most divergent from those already routinely studied.…”
Section: Discussionsupporting
confidence: 86%
“…Studies have suggested that associations with complex traits, especially causal variants, are broadly shared across populations 80 . A systematic study with multiple complex traits estimated that more than 80% of causal variants are shared between Europeans and Asians 81 . In another study, TWAS on asthma using eQTL models trained on data from Europeans and Africans gave broadly similar results 82 .…”
Section: Discussionmentioning
confidence: 99%
“…As the genetic information available from diverse populations increases, we can specifically map the genetics of traits in different populations and more precisely define disease risk on an individual basis 167 , 168 . However, we emphasize that environmental and social factors are major determinants of disease risk that often contribute more than genetics, and thus must be prioritized.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%